2002
DOI: 10.1002/cjce.5450800614
|View full text |Cite
|
Sign up to set email alerts
|

Linear Viscoelastic Properties of Suspensions of Rigid Hairy Particles in a Polymeric Matrix

Abstract: The aim of this work is to use a recently developed statistical model of dispersions with non‐hydrodynamic interactions (Dagréou et al., 2002) to describe the linear viscoelastic properties of suspensions of rigid hairy particles in a polymeric matrix. We first present numerical simulations of our model applied to this system; we demonstrate that taking physical interactions into account allows one to predict the complex relaxation behaviour of filled polymers. We then compare the statistical model to experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…We tested this theoretical approach in the case of polystyrene filled with rigid hairy particles [21]. We showed a reasonable agreement between the experimental results and the theoretical predictions, up to a volume fraction close to percolation.…”
Section: Modeling Of the Linear Viscoelastic Properties Of Emulsions supporting
confidence: 64%
“…We tested this theoretical approach in the case of polystyrene filled with rigid hairy particles [21]. We showed a reasonable agreement between the experimental results and the theoretical predictions, up to a volume fraction close to percolation.…”
Section: Modeling Of the Linear Viscoelastic Properties Of Emulsions supporting
confidence: 64%
“…More recently, interest has focused on the development of nanocomposites. In this case, the fillers can be organic or inorganic nanosized particles: silica particles, mica, and more recently carbon nanotubes. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, another explanation is required for the PBMA–SiO 2 system. Dagreou et al examined a secondary relaxation process for a suspension of polymer‐grafted solid particles in a viscoelastic matrix using a numerical simulation, where it was found that the secondary relaxation was shifted to higher frequencies as the particle size was decreased 24. In our system, an increase in Φ silica means a decrease in size of the polymer/silica composite particle, because the grafted PBMA chains become shorter.…”
Section: Resultsmentioning
confidence: 84%
“…6(b)), PBMA/SiO 2 exhibits a gel‐like behavior in the low‐frequency range instead of a crossover ( G ′ ≈ G ″ ∝ ω 0.5 ) 11, 26. This type of gel‐like behavior has been widely seen in nanocomposites consisting of non‐grafted silica particles in polymer matrices, because an interfacial layer formed by the polymer chains adsorbed on the particles (bound polymer), provides a steric repulsion between the particles (hereafter referred to as a repulsion effect) 24, 30–32. At Φ silica = 0.17 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation